Reflections on ‘Towards a Critical White Theology’: Towards a Critical White Theology, edited by Al Barrett, Jill Marsh, and Anthony G. Reddie, Abingdon and New York, Routledge, 2025, 420pp., £145.00 (hardback), ISBN 978-1-0329-5607-7 - Judson, Tim (Black theology, 2025)
Towards a Critical White Theology is a landmark text that tentatively begins to offer some constructive postures and paradigmatic shifts for discerning and dismantling Whiteness, for the sake of greater equity and faithfulness to the God revealed in Jesus Christ. Various authors (from the USA, UK and New Zealand) engage in a range of fields, including biblical studies, church history, education and formation, mission, church life, Whiteness in the USA, as well as public life in general, exposing the far-reaching tendrils of Whiteness whilst carefully proposing some irenic steps forward that must be taken by White people. Essays unpack experiences and emphases from a range of people who consider the positionality of modern racialisation as a critical factor that White people must recognise in themselves if the problems of racism and far-right extremism are to be resisted today.